Personal Branding of Erika Richardo as a Content Creator on Instagram - Sari, Tina Puspita; Octaviani, Vethy; Dianthi, Martha Heriniazwi (Social Sciences Journal, 2025)
The rapid advancement of communication technology has significantly influenced the way individuals build their personal brand, particularly through visual platforms such as Instagram. Erika Richardo, a young Indonesian painter and content creator, is one example of how personal branding can be developed creatively and consistently in the digital space. This study aims to describe Erika Richardo’s personal branding strategy through her Instagram account @erikarichardo using Peter Montoya’s eight principles of personal branding: specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. The research uses a qualitative descriptive content analysis method, with data collected through observation, documentation, and literature review. The findings show that Erika applies all eight principles in shaping her personal brand. She stands out through her artistic focus on unique painting media, consistent content uploads, and inspirational storytelling. Her branding reflects authenticity, leadership in community projects, and a strong connection between her online persona and real-life values. By maintaining consistent visual identity and interacting with her audience, Erika has successfully positioned herself as an inspirational and professional young artist. This research contributes to a broader understanding of how personal branding can be effectively implemented by creative individuals through social media platforms.